Desenvolvimento de uma estrutura sanduíche de base polimérica, produzida com resíduos das indústrias de mineração e metalurgia, para aplicação como painel divisório de ambientes internos na construção civil - MIRANDA, Rossana Martins (Universidade Federal do Pará, 2017)
The rechearch proposed to use solid wastes from kaolin and bauxite mining and metallurgical regional industries in a composite of sandwich structure to apply as internal divider panel environments. The blade was of unsaturated polyester matrix, double jute fabric and, kaolin waste (20 wt% polyester) and, the core, of polyurethane expansive and red mud (bauxite waste at process to get alumina), from 0 to 50 wt% PU (increasing by 10 to 10 wt%), in a total of 6 different treatments). The tests carried out were: blade density (ASTM C271/271M – 11), sandwich structure bulk density apparent, sandwich structure porosity, tensile test on the blade (ASTM D5083-10), flatwise tensile test on sandwich structure (ASTM C297/C297M - 04), edgewise compressive test on sandwich structure (ASTM C364/C364M–07), flatwise compressive test on sandwich structure (ASTM C297/C297M - 04), 3-point flexural test on sandwich structure (ASTM D7250/D7250M – 06 e ASTM C393/C393M – 11), Charpy impact test on sandwich structure (ASTM D6110 – 10), flammability test on blade and on sandwich structure (UL 94 - 96) and sound transmission loss test on sandwich structure (ISO 140-3:1995 - E). The results indicated that the choise of polymeric matrices was suitable to reduce weight of such structure mainly the use of a PU expansive. Increasing red mud not contributed to significant increase of sandwich structure bulk density apparent. Kaolin waste reinforcement increased resistance to blade on tensile test. Red mud reinforcement reduced sandwich structure resistance on flatwise tensile, flexural and impact tests. Increasing of red mud didn’t influenced sandwich structure edgewise compressive and flatwise compressive tests but, but it´s use at this sandwich structure, decreased their resistance at the first test and increased at the second test. The PU high flammability was delayed for being cloistered by two blades of polyester and kaolin, proving flame retardant property of kaolin waste. And about sound transmission loss test, the increase of red mud increased that until 20% concentration, after this, stabilized at 25 dB (STC) until 50% red mud. The composite, as a whole, presented feature of a sandwich structure, with a low density core, contributing to reduce structure weight and with higher resistant blades, providing it the desired structural feature to be a divider indoor panel.